1998
DOI: 10.1210/jcem.83.2.4584
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble Interleukin-6 Receptor and Biochemical Markers of Bone Metabolism Show Significant Variations During the Menstrual Cycle

Abstract: We examined sequential changes of bone-resorbing cytokines and bone metabolic markers and the effect of ovarian hormones on bone metabolism during the menstrual cycle in 10 healthy Japanese women, aged 22-43 yr, with normal ovarian function. Serum soluble interleukin-6 receptor (sIL-6R) showed a significant variation; a rise during the early and late follicular periods followed by a fall during the early luteal period (P = 0.0423, P = 0.0334) and an increase during the mid and late luteal periods. There were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 51 publications
2
15
1
Order By: Relevance
“…It is possible however, that serum Dpyr better reflects the bone resorption process and is therefore more biologically meaningful. Our results regarding urine Dpyr are similar to Schlemmer et al (6) but different from those of Gorai et al (7,8) The latter reported differences in urine Dpyr between subphases of the cycle, but the patterns of change differ between their two publications. Taken together, the two studies therefore appear to be compatible with our results.…”
Section: Figcontrasting
confidence: 61%
See 4 more Smart Citations
“…It is possible however, that serum Dpyr better reflects the bone resorption process and is therefore more biologically meaningful. Our results regarding urine Dpyr are similar to Schlemmer et al (6) but different from those of Gorai et al (7,8) The latter reported differences in urine Dpyr between subphases of the cycle, but the patterns of change differ between their two publications. Taken together, the two studies therefore appear to be compatible with our results.…”
Section: Figcontrasting
confidence: 61%
“…For purposes of graphing or examining summary values by day, the visits were assigned to 2-day bins, so that a visit on day −14 or −13 was counted as day −14, a visit on day −12 or −11 was counted as day −12, etc. Cycles were divided into FP (day −14 to day −1) and LP (days [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Subphases were defined following Gorai et al (7,8) as early (the first 4 days), mid-(the middle 6 days), or late (the last 4 days).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations